PERAN KELUARGA DALAM PEMBENTUKAN KESEHATAN MENTAL REMAJA MELALUI PENDIDIKAN AGAMA (TELAAH PEMIKIRAN ZAKIAH DARADJAT) - Juhairyah, Nabilah; Suharyat, Yayat (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2023)
The background to the problem of this research is that the problems that occur in teenagers are none other than because their mental health is unhealthy and one of the parties who is also responsible for this is the family. Family is the closest person who can guide and direct teenagers to become individuals who have a good mentality and religious foundation. Zakiah Daradjat is one of the figures who has deep thoughts on this matter. She was the first female Islamic psychology figure to research in depth on mental health in adolescents. This research aims to: (1) To determine the mental health of adolescents according to Prof. Dr. Zakiah Daradjat, (2) To find out the role of the family in shaping adolescent mental health through religious education according to Prof. Dr. Zakiah Daradjat. This research is a type of library research with documentation data collection methods and data analysis methods using descriptive analysis, while the data sources used by researchers consist of primary sources such as books by Zakiah Daradjat, and secondary sources, namely books and other documents. The research results show that: (1) The influence of the family environment is very large on the formation of adolescent mental health. What families can do include: understanding teenagers, being a good listener to teenagers, not interfering in teenagers' personal affairs, and avoiding punishment and threats to teenagers. (2) Islamic religious education carried out in the family environment is a very important force in the formation of adolescent mental health. With a healthy mind, juvenile delinquency can be prevented. Families must be able to create inner peace for their children who are in their teens. Such as providing understanding, advice, guidance on the problems being faced by teenagers through Islamic religious education provided in the family environment so that they avoid ongoing mental disorders.